DECORATIVE PAINTING AS A MEANS OF TRANSLATING CULTURAL SEMANTIC NARRATIVE - VASYLIEVA, K. V.; KOLOSNICHENKO , O. V. (Art and Design, 2024)
Purpose. The research involves analyzing folk decorative painting and transferring its most typical compositional techniques and characteristics into souvenir items. Methodology. To achieve the research goal, a comprehensive approach was employed, utilizing general scientific methods of literature analysis and visual examination of historical materials and contemporary souvenir products. Results. During the research, the features of decorative painting, its techniques, and methods were studied; the morphological components of decorative painting and the ways of interpreting its elements were analyzed. Scientific novelty. The study highlights the cultural and historical significance of decorative painting in the design of souvenir products. A comparative analysis of various types of decorative painting has been conducted and systematized; the compositional elements employed in the creation of souvenir product designs have been analyzed. Practical significance. The research focuses on assessing the feasibility of incorporating elements of decorative painting into souvenir product design and highlights the issue of transmitting semantic narratives that contribute to enhancing the cultural value and aesthetic appeal of contemporary souvenir items.